The Influence of Price Perception, Product Quality, and Café Atmosphere on Purchase Decisions at Teman Kami Space - Mubarok, Syachrul; Soviyan Munawar; Wufron, Wufron (Cv. Syntax Corporation Indonesia, 2025)
The café industry in Indonesia is experiencing significant growth in line with changes in consumer behavior, especially young people who not only visit cafes to enjoy food and drinks, but also to work, socialize, and enjoy a comfortable atmosphere. This phenomenon creates a challenge for café business actors to not only focus on product quality and price, but also on creating an attractive atmosphere. Teman Kami Space, which is located in the coastal area of Karangpapak Beach, Garut, is a modern-classic concept café with an open feel that takes advantage of the beach view, but it is not empirically known what factors are the most dominant influencing consumers' purchasing decisions. This study aims to find out how much the effect and contribution of price perception, product quality, and café atmosphere in influencing consumer purchase decisions at Teman Kami Space cafes. The quantitative research used in this study is multiple linear regression analysis. To collect information, questionnaires were distributed to one hundred respondents who were selected by purposive sampling or price perception. The results showed that consumers' views on price and product quality did not have a significant effect on purchase decisions, while the variables of café atmosphere had a positive and significant influence. These findings indicate that consumers prioritize the comfort and atmosphere of the café or café atmosphere over price factors and product quality in making purchase decisions. Therefore, café management is advised to continue to optimize the atmosphere of the café by improving comfort, interior design, and service so that consumers are encouraged to linger and increase the possibility of making a purchase.